Early administration of adalimumab for paediatric uveitis due to Behçet's disease - Tomona Hiyama; Yosuke Harada; Takehiko Doi; Yoshiaki Kiuchi (BMC, 2019)
Abstract Background Behçet's disease is a chronic inflammatory multisystem disorder that is characterised by oral and/or genital ulcerations as well as intraocular inflammation. Recurrent retinal vasoocclusive episodes and macular involvement may lead to severe loss of visual acuity. Patients may eventually become resistant to systemic corticosteroid and develop side effects; therefore, other immunosuppressive therapies are needed. Biologic agents are promising for the treatment of Behçet's disease-associated uveitis. Here, we report two cases of paediatric uveitis due to Behçet's disease that were successfully treated by early administration of adalimumab. Case presentation Patient 1 was an 11-year-old girl who presented with right conjunctival injection and photophobia. Patient 2 was a 14-year-old girl who presented with blurry vision in the left eye. Both patients were treated with topical treatment and prednisolone for uveitis; however, relapses occurred during the tapering of prednisolone. The patients were diagnosed with Behçet's disease, and adalimumab therapy was initiated. In both cases, the inflammation was well-controlled by adalimumab administration without local or systemic corticosteroid. Conclusions Adalimumab is effective for treating children with Behçet's disease-associated uveitis. Control of ocular inflammation was achieved without local and systemic corticosteroid, thus preventing further complications.